2021
DOI: 10.3390/agriculture11121223
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Leveling for Paddy Field Preparation with Double Axis Rotary Tillage Accelerates Rice Growth and Economic Benefits

Abstract: In the multiple cropping regions of southern China, straw returning has become a widely practiced agronomic measure for rice cultivation. However, excessive straw often leads to a high proportion of stubble in topsoil, which prolongs the leveling time of the paddy field and delays the transplanting date for rice seedlings. In particular, scholars in this region have successively improved multiple paddy field levelers to realize excellent straw returning and subsequent land preparation synchronously, but the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A recent study has shown that biaxial deep rotary tillage and leveling can enhance the structure of the soil in paddy fields as well as economic benefits (Zhang et al, 2021). In this study, DBRT had lower CF, higher EUE and NEEB than DPURT and PURT.…”
Section: Net Ecosystem Economic Efficiency and Outlookmentioning
confidence: 47%
See 2 more Smart Citations
“…A recent study has shown that biaxial deep rotary tillage and leveling can enhance the structure of the soil in paddy fields as well as economic benefits (Zhang et al, 2021). In this study, DBRT had lower CF, higher EUE and NEEB than DPURT and PURT.…”
Section: Net Ecosystem Economic Efficiency and Outlookmentioning
confidence: 47%
“…The energy output was 7.6-9.2% and 17.7-19.7% higher under DBRT than under DPURT and PURT, respectively, and this was mainly driven by increases in rice grain yield. The higher grain yield under DBRT mainly stemmed from increases in tillage depth, which promoted the deep burial of straw, alleviated the toxic effect of straw decay on rice seedlings and competition for soil N (Shen et al, 2014;Zhang et al, 2021), and thus promoted the growth of rice seedlings. The greater tillage depth in DBRT facilitates the growth of the roots of rice plants at greater soil depths, which enhances nutrient uptake (Garnett et al, 2009;Lynch, 2013).…”
Section: Energy Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct-seeding rice is a popular agronomic practice in Asia, North America, and Europe, because it eliminates the labor-intensive steps of raising and transplanting rice seedlings [ 1 , 2 , 3 ]. The agricultural management of direct-seeded rice also tends to be more efficient in terms of mechanized tillage, sowing, and harvesting, allowing a larger land area to be cultivated with less labor [ 4 ]. However, direct-seeded rice is still primarily split-fertilized, particularly in China, where a base fertilizer and multiple topdressing are often required [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, threatened food security due to rapid worldwide population growth has led to efforts in increasing agricultural food production [1,2]. However, highyielding agriculture leads to plenty of crop residues being left in the field after harvest, which is detrimental to seeding operation, seed germination, and early plant growth [3][4][5][6]. Agricultural producers thus have been seeking suitable tillage operations to alleviate the problems of excessive crop residues.…”
Section: Introductionmentioning
confidence: 99%